Investigating the Effects of Spacing on Working Memory Training Outcome: A Randomized, Controlled, Multisite Trial in Older Adults. (29th July 2019) - Jaeggi, Susanne M; Buschkuehl, Martin; Parlett-Pelleriti, Chelsea M; Moon, Seung Min; Evans, Michelle; Kritzmacher, Alexandra; Reuter-Lorenz, Patricia A; Shah, Priti; Jonides, John
Abstract: Objective: The majority of the population will experience some cognitive decline with age. Therefore, the development of effective interventions to mitigate age-related decline is critical for older adults' cognitive functioning and their quality of life. Methods: In our randomized controlled multisite trial, we target participants' working memory (WM) skills, and in addition, we focus on the intervention's optimal scheduling in order to test whether and how the distribution of training sessions might affect task learning, and ultimately, transfer. Healthy older adults completed an intervention targeting either WM or general knowledge twice per day, once per day, or once every-other-day. Before and after the intervention and 3 months after training completion, participants were tested in a variety of cognitive domains, including those representing functioning in everyday life. Results: In contrast to our hypotheses, spacing seems to affect learning only minimally. We did observe some transfer effects, especially within the targeted cognitive domain (WM and inhibition/interference), which remained stable at the 3-month follow-up. Discussion: Our findings have practical implications by showing that the variation in training schedule, at least within the range used here, does not seem to be a crucial element for training benefits.